Dedifferentiated Low-Grade Osteosarcoma, Outcome with or Without Chemotherapy: A Systematic Review - Pacheco M; Guzmán R; Bonilla P (Orthopedic Research and Reviews, 2023)
Marina Pacheco,1,2 Rodolfo Guzmán,3 Patricia Bonilla4 1Department of Pathology, Complejo Hospitalario Metropolitano CSS, Social Security Fund, Panama, Panama; 2Sistema Nacional de Investigación; Secretaria Nacional de Ciencia, Tecnologia e Innovación, Panama, Panama; 3Department of Pathology, Hospital San Juan de Dios CCSS, San Jose, Costa Rica; 4Department of Orthopedics, Hospital del Niño Dr. José Renán Esquivel, Panama, PanamaCorrespondence: Marina Pacheco, Departamento de Patología, Complejo Hospitalario Metropolitano Dr. Arnulfo Arias Madrid CSS, Avenida José de Fábrega y Simón Bolivar, Bella Vista, Panama, Panama, Tel +507 503 6219, Email mpacheco@css.gob.paAbstract: The treatment of low-grade osteosarcomas is surgical resection with wide margins. In instances of dedifferentiation, a therapeutic paradigm similar to that of conventional high-grade osteosarcoma has not been adequately evaluated in these neoplasms. The main objective of this review was to define whether the addition of chemotherapy to surgical treatment has an impact on the survival of patients with dedifferentiated low-grade osteosarcomas. Secondary objectives were to observe the degree of histological response to neoadjuvant chemotherapy and to describe the percentage of de novo dedifferentiation. A systematic search of articles including dedifferentiated low-grade osteosarcomas, published between 1980 and 2022 was carried out in the PubMed, Cochrane and Scielo databases. A qualitative synthesis of the results was performed. Twenty-three articles comprising 117 patients were included. The survival of patients treated with surgery alone and surgery with chemotherapy was not statistically significant between the two groups. A good histological response was seen in 20% of specimens treated with neoadjuvant chemotherapy. De novo dedifferentiation was seen in approximately a fifth of low-grade osteosarcomas. The evidence available suggests that the addition of chemotherapy does not have an impact on the survival of patients with low-grade dedifferentiated osteosarcomas.Keywords: dedifferentiated, osteosarcoma, parosteal osteosarcoma, low-grade central osteosarcoma